2007
DOI: 10.1038/sj.jp.7211682
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A: an early and accurate marker of neonatal early-onset sepsis

Abstract: Objectives: To evaluate the accuracy of serum amyloid A (SAA), an acute phase protein in the detection of neonatal early-onset sepsis, by means of a fast automated SAA kit.Study Design: Full-term infants <72 h of age, who had risk factors and/or were suspected of having sepsis, were eligible for study. The levels of SAA were taken at 0, 24 and 48 h post sepsis evaluation. Thirty matched infants served as a control group for comparing SAA concentrations.Results: Of 104 infants eligible for entry to the study, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 19 publications
2
47
0
2
Order By: Relevance
“…31 They established that SAA had higher levels, and rose earlier and sharper than CRP. 10 In our study, we found that SAA had higher levels during the initial and 48-h evaluation of infants with sepsis. We have also shown that it declined faster than CRP and PCT during the follow-up of sepsis.…”
Section: Saa Crp and Pctsupporting
confidence: 47%
See 1 more Smart Citation
“…31 They established that SAA had higher levels, and rose earlier and sharper than CRP. 10 In our study, we found that SAA had higher levels during the initial and 48-h evaluation of infants with sepsis. We have also shown that it declined faster than CRP and PCT during the follow-up of sepsis.…”
Section: Saa Crp and Pctsupporting
confidence: 47%
“…SAA has been shown to be useful in various acute diseases (bacterial, viral, traumatic, rheumatic and ischemic heart disease) and also in the diagnosis of sepsis in neonates. 3,[9][10][11] Although the data about its use in diagnosis of neonatal sepsis is limited, recently it has been suggested as a superior marker compared with CRP. 12 CRP is a protein produced by the liver in response to inflammatory and/or infectious stimuli, and for this reason it is regarded as an acute-phase protein.…”
Section: Introductionmentioning
confidence: 99%
“…Warning signs and symptoms are often subtle and can easily be confused with noninfective causes such as apnea, hypothermia, and acute exacerbation of chroniclung disease. So that hematological and biochemical markers such as immature/total neutrophil ratio, platelet count, C-reactive protein (CRP), various cytokines, procalcitonin (PCT), and tumornecrosis factor- α (TNF- α ) have been proposed as being useful indicators for early identification of septic infants [14]. Recently, SAA that refers to a group of polymorphic apolipoproteins 12–14 kDa, mainly produced by the liver, has been proposed as a new discriminative marker of bacterial infection [1, 36].…”
Section: Introductionmentioning
confidence: 99%
“…Levels of SAA increase up to 1000 fold in the 8 to 24 hours after the onset of inflammation. Serum amyloid A has been shown to be useful in various acute diseases (bacterial, viral, traumatic, rheumatic, and ischemic heart disease) and also in neonatal sepsis [16][17][18]. Recently, we have shown that SAA might be used as an accurate marker in addition to clinical and laboratory findings in the diagnosis of NEC [19].…”
mentioning
confidence: 98%